Are interventions effective at improving driving in older drivers?: A systematic review - Castellucci, H. I. (2020)
Background With the aging of the population, the number of older drivers is on the rise. This poses significant challenges for public health initiatives, as older drivers have a relatively higher risk for collisions. While many studies focus on developing screening tools to identify medically at-risk drivers, little research has been done to develop training programs or interventions to promote, maintain or enhance driving-related abilities among healthy individuals. The purpose of this systematic review is to synopsize the current literature on interventions that are tailored to improve driving in older healthy individuals by working on components of safe driving such as: self-awareness, knowledge, behaviour, skills and/or reducing crash/collision rates in healthy older drivers. Methods Relevant databases such as Scopus and PubMed databases were selected and searched for primary articles published in between January 2007 and December 2017. Articles were identified using MeSH search terms: ("safety" OR "education" OR "training" OR "driving" OR "simulator" OR "program" OR "countermeasures") AND ("older drivers" OR "senior drivers" OR "aged drivers" OR "elderly drivers"). All retrieved abstracts were reviewed, and full texts printed if deemed relevant. Results Twenty-five (25) articles were classified according to: 1) Classroom settings; 2) Computer-based training for cognitive or visual processing; 3) Physical training; 4) In-simulator training; 5) On-road training; and 6) Mixed interventions. Results show that different types of approaches have been successful in improving specific driving skills and/or behaviours. However, there are clear discrepancies on how driving performance/behaviours are evaluated between studies, both in terms of methods or dependent variables, it is therefore difficult to make direct comparisons between these studies. Conclusions This review identified strong study projects, effective at improving older drivers' performance and thus allowed to highlight potential interventions that can b